Taxation of MNE profits in an R&D driven economy: Beneficial tax havens and minimum taxes - Malte Lüttmann (The World Economy, 2024)
Research and development (R&D) by multinational enterprises (MNEs) generates substantial positive cross-country spillovers. With R&D incentives primarily provided by the MNEs' host countries, these nations bear the entire cost of incentivising R&D but only reap a fraction of the benefits, resulting in inefficiently low R&D incentives and investment from a global perspective. Allowing MNEs to shift their profit to a tax haven shelters the firms' profit from foreign taxation and increases the net returns to R&D without reducing the domestic tax base. In this setting, tax havens can be welfare beneficial because they help to internalise the positive cross-country spillovers of R&D. The optimal effective minimum tax balances a reduction in wasteful profit shifting and more efficient R&D incentives for MNEs. Regardless of the welfare effect of R&D, a strictly positive minimum tax is optimal for each country. Uncoordinated minimum taxes may be excessively high, if R&D investment has a strong impact on productivity. Under certain circumstances, IP boxes are a welfare-improving substitute for tax havens.
Keywords: 330; corporate taxation; intellectual property; minimum tax; multinational firms; optimum taxation; patent box